Pronouns Beyond the Binary: The Change of Attitudes and Use Over Time. Issue 4 (August 2021) - Gustafsson Sendén, Marie; Renström, Emma; Lindqvist, Anna
Gender-inclusive language, such as the Swedish pronoun hen, may aid in breaking a binary notion of gender and avoid sexism. The present study followed the implementation of a gender-inclusive third-person pronoun singular (hen) in Swedish in two surveys with representative samples in 2015 (at the time when hen was introduced in the official Swedish dictionary; N = 1212) and in 2018 (N = 2009). The surveys comprised measures of attitudes toward, and use of, hen as well as possible predictors such as area of residence, age, preferred pronoun, political orientation, and interest in gender issues. Results showed that attitudes toward hen became more positive and that use of hen increased between 2015 and 2018. About half of the population used hen in their communication in 2018, which is a 14-percentage-point increase from 2015. Younger age, she or hen as preferred pronoun, political left-wing orientation, and interest in gender issues predicted a more positive attitude and a more frequent use. Furthermore, the positive change between 2015 and 2018 was larger among younger people, indicating that hen will remain in the Swedish language. The present research is unique in that it follows a gender-fair language initiative during its implementation in representative samples, thereby providing insights for social movements aiming for gender-fair language. We also discuss the theoretical implications of a gender-inclusive pronoun in comparison with past studies on gender-fair language.